DNA damage and protein oxidation associated with ageing correlate with cognitive dysfunction in a Malaysian population. (2nd September 2018) - Abdul Sani, Nur Fathiah; Ahmad Damanhuri, Mohd Hanafi; Amir Hamzah, Ahmad Imran Zaydi; Abu Bakar, Zulzikry Hafiz; Tan, Jen-Kit; Nor Aripin, Khairun Nain; Mohd Rani, Mohd Dzulkhairi; Noh, Nor Azila; Shamaan, Nor Aripin; Razali, Rosdinom; Mohd Yusof, Yasmin Anum; Mazlan, Musalmah; et al.
Abstract: Ageing is associated with increased oxidative stress accompanied by cognitive decline. The aim of this study was to evaluate oxidative stress biomarkers and their possible relationship with cognitive performances during ageing among the Malay population. Approximately 160 healthy Malay adults aged between 28 and 79 years were recruited around Selangor and Klang Valley. Cognitive function was assessed by Montreal Cognitive Assessment (MoCA), forward digit span (FDS), backward digit span (BDS), digit symbol, Rey Auditory Verbal Learning Test immediate recalled [RAVLT(I)] and delayed recalled [RAVLT(D)], and visual reproduction immediate recalled (VR-I) and delayed recalled (VR-II). DNA damage, plasma protein carbonyl and malondialdehyde (MDA) levels were also determined. Cognitive function test showed significant lower scores of MoCA, BDS, RAVLT(I), RAVLT(D), digit symbol, VR-I, and VR-II in the older age group (60 years old) compared with the 30-, 40-, and 50-year-old group. The extent of DNA damage was sequential with age: 60 > 50 > 40 > 30, whereas protein carbonyl was higher in 40-, 50-, and 60-year-old groups compared with the youngest group (30 years old). However, the MDA level was observed unchanged in all age groups. Approximately 21.88% of the participants had cognitive impairment. Multiple logistic regression analysis revealed that DNA damage and protein carbonyl levels are predictors for cognitive impairment in healthy Malays. In conclusion, cognitive decline occurred in healthy adult Malay population at an early age of 30 years old with corresponding higher DNA damage and protein oxidation.